Two‐Step Sequence Multicomponent Synthesis/Reductive Rearrangement of 2‐Acyl‐2, 3‐dihydrofurans for Modular Assembly of Annulated 4H‐Pyrans. Issue 15 (9th July 2021) - Demidov, Maxim R.; Osipov, Dmitry V.; Korol'kov, Konstantin A.; Osyanin, Vitaly A.
Abstract: A variety of trans ‐2‐acyl‐2, 3‐dihydrofurans have been assembled from readily available structurally diverse precursors and then rearranged into a series of annulated 4 H ‐pyrans by the action of Sm/TMSCl or Zn/ZrCl4 redox systems. Present synthetic sequence is claimed as a modular approach to hetero‐ and carbon‐fused 4 H ‐pyrans. The rearrangement involves the SET reduction of carbonyl group to carbene followed by rare type of [1, 2]‐aroxyl shift. Synthetic toolbar was enriched with the use of the Zn/ZrCl4 redox system. Abstract :